(untitled) (Research, Society and Development, 2021)
This study aims to present new perspectives of educational management and its application in the state of Piauí. To this end, it employed a literature review of exploratory descriptive using as source the Brazilian Journal of Education - RBE - indexed in SciELO database, as well as articles from other bases, monographs, dissertations and books. Was also used analysis type documentary of publications relating to the web pages officers of Piauí. Democratization in school management is a milestone for the new educational system, with the legal basis to the Brazilian Federal Constitution and the Law of Guidelines and Bases of National Education. In the Piauí, the practice of innovation in management education, especially basic education, comes putting the state ahead of participation in educational programs and encourage the training of managers. Therefore, the State of Piauí is a propellant in terms participatory management in education, encouraging schools to participate in programs such as School Management Award and also investing in the training of managers in order to maintain the commitment to education incorporating new strategies to manage the way, with the aim of supporting and improving knowledge management tools.